The effectiveness of multimedia courseware in learning data modelling concepts / Nor Azzyati Hashim and Nurul Syazwani Jamaludin - Hashim, Nor Azzyati; Jamaludin, Nurul Syazwani (UiTM Cawangan Perlis, 2018)
Data modelling is a tough topic for students to learn in database courses or database related courses. The use of multimedia courseware with student-centred learning capability can help to enhance students learning and improve achievement on the subject matter. Accordingly, the objective of this paper is to evaluate the effectiveness of using multimedia courseware as a supplemental tool to enhance students learning in data modelling concepts among Bachelor of Information Technology students at Universiti Teknologi MARA, Perlis Branch. To achieve this objective, multimedia courseware was developed with three main sections: pre-test, tutorial and post-test. The courseware then tested on 20 students that have previously learned about data modelling. From the findings, it is discovered that the students’ post-test marks increased after learning using the tutorial courseware when compared with their pre-test marks. The finding results also showed a significant statistical difference between pre-test and post-test marks after using the tutorial. These findings indicate that the students have made significant improvement after learning with the multimedia courseware. As a conclusion, the multimedia courseware indeed can be effective to be used as a supplemental learning tool to enhance students learning and achievement in data modelling concepts thus, overcome the limitations of teacher- centred learning in a classroom environment.